2006
DOI: 10.1348/135910705x59951
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and self‐rated health: Interactive effects of activity in work and leisure domains

Abstract: These findings highlight the importance of leisure physical activity for employees in sedentary jobs, but suggest that other factors (such as adverse environmental conditions) may underlie the lower SRH associated with physically demanding work. The results also indicate that, irrespective of job activity level, younger individuals benefit more from leisure physical activity than older ones. Thus, the study informs interventions designed to improve the health of employees through increased physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 65 publications
(118 reference statements)
2
19
2
2
Order By: Relevance
“…A longitudinal study by Parkes et al (2) found no interaction between age and physical work demands as risk factors for worsened SRH, but this study was limited by very low statistical power with only 314 participants. Aittomäki et al (12) found that the association of physical work demands with poor health was stronger among older than younger employees (12); however, the cross-sectional study design did not permit causal inference.…”
Section: Does Age Modify Association Of Physical Demands With Health?mentioning
confidence: 78%
See 1 more Smart Citation
“…A longitudinal study by Parkes et al (2) found no interaction between age and physical work demands as risk factors for worsened SRH, but this study was limited by very low statistical power with only 314 participants. Aittomäki et al (12) found that the association of physical work demands with poor health was stronger among older than younger employees (12); however, the cross-sectional study design did not permit causal inference.…”
Section: Does Age Modify Association Of Physical Demands With Health?mentioning
confidence: 78%
“…Exposure to high physical work demands, ie, demanding body postures, repetitive movements, and heavy lifting, has been found to increase the risk for subsequent development of poor self-rated health (SRH) (1)(2)(3). SRH is a powerful global indicator of health as it strongly predicts morbidity and mortality (4)(5)(6).…”
mentioning
confidence: 99%
“…Bagi responden yang pulang setiap hari, waktu untuk berolahraga menjadi kendala karena sudah lelah selama seharian bekerja, sementara bagi yang tinggal di lokasi saat selesai bekerja lebih memilih istirahat dibandingkan melakukan kegiatan olahraga. Penelitian Parkes, 15 menyatakan bahwa olahraga secara teratur dapat menurunkan berat badan, mengurangi stres, mengendalikan kadar gula darah, memperbaiki kadar insulin, dan mencegah diabetes tipe 2.…”
Section: Karakteristik Individuunclassified
“…Moreover, negative self-rated health is associated with higher frequency of chronic diseases 10 , smoking over 20 cigarettes a day, insufficient levels of physical activities 11,12 , low weight or obesity 13 , female sex, advanced age, low educational background and compromised health 14 . Some studies have shown that physically active men present better self-rated health compared to the insufficiently active ones [15][16][17] . Others point out regular practice of physical activity as predictor of positive self-rated health 15 , and, therefore, it is believed that different associated factors may boost even more the wellness of physically active individuals, reinforcing the need of research which evidences this correlation.…”
Section: Introductionmentioning
confidence: 99%
“…in research followed for five years and carried out with middle-aged adults, they evidenced the association between practice of leisure physical activity and positive self-rated health, being more evident among the younger ones 16 . Similar data were found in the investigation in 15 countries members of the European union 17 .…”
mentioning
confidence: 96%